Fabrication of Shape‐Controlled Palladium Nanoparticle‐Decorated Electrospun Polypyrrole/Polyacrylonitrile Nanofibers for Hydrogen Peroxide Coalescing Detection. Issue 22 (12th September 2017) - Kim, Wooyoung; Shin, Dong Hoon; Jun, Jaemoon; Kim, Jae Hyun; Jang, Jyongsik
Abstract: Shape‐controlled palladium nanoparticle‐decorated electrospun polypyrrole/polyacrylonitrile nanofibers (Pd_PPy/PAN NFs) are fabricated by electrospinning, vapor deposition polymerization (VDP), and electrodeposition. The electrospun PAN NFs are used as the framework for a composite nanomaterial. To make the material electrically conductive, the framework is coated with PPy by VDP. As‐prepared PPy/PAN NFs are used as the working electrode during electrodeposition of Pd. During Pd introduction, the presence of sulfuric acid in the electrolyte influences the shape of the Pd nanoparticles. Sulfate ions prevent the growth of the Pd, resulting in nanoparticles with sharp features. The fabricated Pd_PPy/PAN NFs are then incorporated as the active element in an electrochemical hydrogen peroxide (H2 O2 ) biosensor. Tailoring the morphology of the Pd nanoparticles enables a minimum detectable limit of 1 × 10 −9 m H2 O2, which is sufficiently low for monitoring diseases related to H2 O2 concentration, such as Parkinson's disease and Alzheimer's disease. The low detection limit is achieved by coalescing detection of Pd and PPy. Abstract : Shape‐controlled palladium nanoparticle‐decorated electrospun polypyrrole/polyacrylonitrile nanofibers (Pd_PPy/PAN NFs) are fabricated by electrospinning, vapor phase deposition, and electrodeposition. The morphology of Pd is easily modified by controlling the sulfuric acid concentration in the electrolyte. The Pd_PPy/PAN NFs‐based H2 O2 sensor exhibits low minimum detectable limit of 1 × 10 −9 m .